Mental state of COVID-19 patients in the mobile cabin hospital and related nursing countermeasures (方舱医院内新型冠状病毒肺炎患者的心理状态及护理对策) - MI Yuehua (米跃华); ZHAO Chunhua (赵春华); YAN Haichun (闫海春); SUN Hongyan (孙红艳) (中西医结合护理, 2022)
Objective To investigate the effect of psychological nursing measures on mental state of COVID-19 patients in the mobile cabin hospital. Methods A Survey of psychological assessment was conducted to 400 COVID-19 patients who were admitted to the mobile cabin hospital between April 15th, 2022 and May 20th, 2022. The individualized psychological nursing interventions were carried out. Results There were 391(97. 75%) cases of mild anxiety and 9(2. 25%) cases of moderate anxiety. After implementation of psychological nursing interventions, all patients had good compliance with treatment, and no case of adverse events was reported. Conclusion Implementation of early psychological assessment and targeted psychological nursing interventions maybe helpful to improve the treatment compliance and recovery of COVID-19 patients. (目的 探讨心理护理措施在方舱医院内新型冠状病毒肺炎患者中的应用效果。方法 选取2022年4月15日—5月20日方舱医院收治的400例新型冠状病毒肺炎患者, 开展心理评估, 并针对性实施个体化心理护理措施。结果 400例患者中391(97. 75%)例存在轻微焦虑, 9(2. 25%)例患者存在中度焦虑。通过实施个性化心理护理措施, 患者均能保持情绪稳定, 配合治疗, 无不良事件发生。结论 早期评估新型冠状病毒肺炎患者的心理状态, 制定相应的心理护理措施, 有助于提高患者治疗依从性, 促进患者早日康复。)